2005
DOI: 10.1016/j.gastro.2005.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-13 Is the Key Effector Th2 Cytokine in Ulcerative Colitis That Affects Epithelial Tight Junctions, Apoptosis, and Cell Restitution

Abstract: IL-13 was identified as an important effector cytokine in UC that impairs epithelial barrier function by affecting epithelial apoptosis, tight junctions, and restitution velocity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
714
7
12

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,003 publications
(795 citation statements)
references
References 0 publications
30
714
7
12
Order By: Relevance
“…Expression of the major tight junction proteins is also reduced in the intestines of GC-C deficient mice. Luminal antigens permeate the defective barrier, promote inflammation, and damage the intestinal mucosal architecture [18,41] . These studies suggest a critical role of GC-C signaling in preserving the intestinal integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of the major tight junction proteins is also reduced in the intestines of GC-C deficient mice. Luminal antigens permeate the defective barrier, promote inflammation, and damage the intestinal mucosal architecture [18,41] . These studies suggest a critical role of GC-C signaling in preserving the intestinal integrity.…”
Section: Discussionmentioning
confidence: 99%
“…68 The drop in TER in secondary infections with H. polygyrus, was accompanied by a small increase in the epithelial expression of the pore-forming claudin-2, and the barrier defect was absent in IL-13Ra1 ¡/¡ mice. 69 Increased IL-13 production following infection with helminths can be from innate 70 or adaptive immune cells, 71 and while IL-13 has been shown to directly decrease the barrier function of epithelial monolayers in vitro, 24,72 it is unclear if helminth-evoked IL-13 targets the epithelium directly or via other immunoregulatory activities.…”
Section: Increased Epithelial Permeability Triggered By Infection Witmentioning
confidence: 99%
“…49 Dysregulation of tight junction proteins contributes to barrier loss in patients with intestinal diseases. For instance, claudin-2, a pore forming tight junction protein, was significantly upregulated in CD, 47 UC, 50 and in patients with collagenous colitis 51 by a Th2 cell cytokine (IL-13)-dependent mechanism. Occludin and select sealing claudins (claudins-1, 3, and 4) were reduced in expression or redistributed in intestinal permeability disorders, including ischemic injury, 8 CD, 47 and UC.…”
Section: Defect Of the Intestinal Mucosal Barrier In Intestinal Disormentioning
confidence: 99%
“…47,48,50 Thus, we hypothesized that the ClC-2 chloride channel also has a critical role in the regulation of colonic barrier function under inflammatory conditions. Our recent study found that the severity of experimental colitis was significantly increased in the ClC-2 ¡/¡ mice as compared with WT mice.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%